Coronary Embolism Caused by Massive Intraventricular Thrombus in a Young Patient with Thrombophilia and Drug-Induced Dilated Cardiomyopathy - Grigoroaea Ciprian; Haja Ioana; Păcurar Delia; Rodean Ioana Patricia (Journal of Cardiovascular Emergencies)
Cardiac thrombi are often incidental findings on cardiac imaging and typically appear as uniform echo-densities. They develop in areas of blood flow stasis, particularly in structurally abnormal chambers such as in dilated cardiomyopathy. Their differential diagnosis includes vegetations and tumors, therefore accurate identification is critical for appropriate management.